ACADEMIC ENTREPRENEUR DEVELOPMENT (MANAGEMENT PTKIS PERSPECTIVE) - Rahman, Kholilur; Fanani, Ahmad Aziz (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2023)
Recently, the phenomenon of paradigm revolution arised in the management of tertiary institutions (both state or private) to become financially more independent institutions, no longer only rely on funding subsidies from the government, but doing for innovating, exploring, and managing the potential "assets" possessed for Realizing the independence of the university. One of the concepts offered in that direction is the development of academic entrepreneurs. This article was intended to describe the development of academic entrepreneurs in the perspective of management, prospects and challenges for PTKIS.The approach of the study was Qualitative methods. While the data collection was carried out through literature studies and other secondary data. The results of the study showed that the development of academic entrepreneurs in the management perspective got prospects, and at the same time got challenges. to react for this, it was recommended that university, especially PTKIS, started mapping readiness to the development of academic entrepreneurs using the scale of readiness calculation or unpreparedness in implementing it.